Title not available in English. - Matos, Ralfo (1995)
Theoretical lssues on population concentration and decentralization in space. The paper focuses the issue of population decentralization in Brazil under a theorical perspective. At first, it was necessary to proceed an analytic description of the historical process of formation of the economic and demographic concentration in the geographic space, emphasizing the importance of some explainning factors, such as: natural resources, stale intervention and aglomeration economies. These factors, later on, begin to act the opposite direction, that is, dispersing economic activities in space. In addition, the focus on population decentralization requires the consideration of other issues, such as the demographic transition and the causes of migration flows from great urban centers to ”secondary cities”. Besides, it is important consider aspects related to the real access both to the land and labor markets of the “core-areas”, which affect the unskilled workers, especially in less developed countries, like Brazil.